1998
DOI: 10.7326/0003-4819-129-10-199811150-00002
|View full text |Cite
|
Sign up to set email alerts
|

Dental and Cardiac Risk Factors for Infective Endocarditis: A Population-Based, Case-Control Study

Abstract: Dental treatment does not seem to be a risk factor for infective endocarditis, even in patients with valvular abnormalities, but cardiac valvular abnormalities are strong risk factors. Few cases of infective endocarditis would be preventable with antibiotic prophylaxis, even with 100% effectiveness assumed. Current policies for prophylaxis should be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
230
1
17

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 408 publications
(258 citation statements)
references
References 26 publications
10
230
1
17
Order By: Relevance
“…Infective endocarditis (IE) is an uncom mon but potentially fatal disease, and while antibiotic prophylaxis prior to some dental procedures was conventional in the United Kingdom (UK) until recently, the tenuous, if not over-emphasised link with dental treatment was beginning to be both scientifi cally challenged, [1][2][3] and acknowledged in civil law. 4 Nevertheless, throughout the history of IE prophylaxis, professional organisa tions have sought to identify and stratify the groups of patients considered to be at risk, as well as list those procedures for which antibiotic cover should be supplied, [5][6][7][8][9][10] although none of them have ever reached complete consensus with each other.…”
Section: Introductionmentioning
confidence: 99%
“…Infective endocarditis (IE) is an uncom mon but potentially fatal disease, and while antibiotic prophylaxis prior to some dental procedures was conventional in the United Kingdom (UK) until recently, the tenuous, if not over-emphasised link with dental treatment was beginning to be both scientifi cally challenged, [1][2][3] and acknowledged in civil law. 4 Nevertheless, throughout the history of IE prophylaxis, professional organisa tions have sought to identify and stratify the groups of patients considered to be at risk, as well as list those procedures for which antibiotic cover should be supplied, [5][6][7][8][9][10] although none of them have ever reached complete consensus with each other.…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper examined the relationship between the risk factors for endocarditis and showed that in a case control study that dental treatment was not a risk factor for infective endocarditis. 18 Whether it is yet time to abandon antibiotic prophylaxis for dental treatment or whether further evidence is required is a matter for the Endocarditis Working Party and similar advisory bodies at national and international level.…”
Section: Researchmentioning
confidence: 99%
“…Strom et al (104) conducted a population-based, case-control study of 273 patients with proven bacterial endocarditis and matched controls. They found no increase in the risk of bacterial endocarditis in patients with valvular abnormalities undergoing dental procedures.…”
Section: Endocarditis Prophylaxismentioning
confidence: 99%